Lipid Fractions, Fatty Acid Profiles, and Bioactive Compounds of Lithospermum officinale L. Seeds - Lyashenko, Svetlana; Yunusova, Svetlana; López‐Ruiz, Rosalía; Vasfilova, Evgeniya; Kiseleva, Olga; Chimitov, Daba; Bahanova, Milada; Bojko, Natalija; Guil‐Guerrero, José Luis (Journal of the American Oil Chemists' Society, 2021)
Seeds of Lithospermum officinale L. from different climatic zones were analyzed for new sources of γ‐linolenic acid (GLA, 18:3n‐6) and stearidonic acid (SDA, 18:4n‐3). Cultured Borago officinalis was also analyzed for comparative purposes. Analyses were conducted for fatty acid (FA) profiles of the glyceride oils from the seeds and in the neutral and polar lipids by gas chromatography (GC); lipid classes by open column chromatography and preparative thin layer chromatography (TLC); and tocopherols, sterols, and phenolic compounds by high‐performance liquid chromatography with diode array detection (HPLC‐DAD), and the later compounds were confirmed by liquid‐chromatography‐mass spectrometry (LC–MS). L. officinale from St. Petersburg Botanical Garden showed the highest percentage of GLA (17.9% of total FA), while wild‐growing L. officinale from the Rostov region contained the highest percentage of SDA (17.2% of total FA). Total FA content ranged from 11.3 to 20.8% of seed weight. Neutral and polar lipids accounted for ~98 and 2.27%, respectively, of total lipids. Five neutral lipid classes were identified (% of NL): triterpene esters (1.3), triacylglycerols (93.1), free FA (1.8), diacylglycerols (1.4), and monoacylglycerols (2.4). The highest tocopherol content was found in samples from Chechen Republic (35.7 mg/100 g), in which the δ isomer was the main component. Samples from the Rostov region had the highest amounts of sterols (83.8 mg/100 g), and Δ5‐avenasterol was the predominant compound in all samples. L. officinale seeds contain high amounts of phenolic compounds (389.9 mg/100 g as upper limit), in which rosmarinic acid is highlighted. Overall, all data suggest the possibility of using L. officinale seed oil in pharmaceutical and cosmetic formulae and as functional food.